Economic burden and risk factors of migraine disease progression in the US: a retrospective analysis of a commercial payer database. (1st November 2020) - Foster, Shonda A.; Chen, Chi-Chang; Ding, Yao; Mason, Oksana; McGuiness, Catherine B.; Morrow, Paula; Ye, Wenyu; Wade, Rolin L.; Smith, Timothy R.; Joshi, Shivang
Abstract: Aims: To evaluate the prevalence and risk factors of migraine progression and to assess the incremental burden of migraine progression on healthcare systems. Materials and methods: Adult patients were required to have a migraine diagnosis in IQVIA's US adjudicated claims database between 1 January 2012 and 30 June 2016, continuous enrollment ≥12 months before and after the index date (i.e. the first observed migraine diagnosis), and ≥1 additional migraine diagnosis claim during the 12-month post-index period. A previously-developed algorithm identified patients with prevention-eligible episodic migraine (EM). All-cause healthcare resource utilization (HCRU) and costs were evaluated at baseline, over the follow-up period and pre/post progression from prevention-eligible EM to chronic migraine. Cox proportional hazards models were used to evaluate risk factors associated with progression. Results, limitations, and conclusions: Of the 125, 436 patients with prevention-eligible EM that were initially identified, 5, 790 (4.6%) were further identified as progressed. Patients who progressed had higher healthcare costs and higher medication use at baseline compared to patients that did not progress. Mean (SD) all-cause total costs per patient per month were $1, 790 ($3, 788), significantly higher in the post-progression period compared to $1, 414 ($2, 456) in the pre-progression period in patients who progressed ( p  < .0001). Younger age, female sex, initial diagnosis by a neurologist, chronic pain, and use of triptans and/or non-specific acute medications were all significant progression risk factors. Results are limited by the use of a heterogeneous population (incident, prevalent, treated, and untreated patients), coding biases, and lack of information on non-prescription drug utilization and plan limits. Limitations aside, there are substantial HCRU and cost burden associated with migraine progression. Younger age, female sex, and the use of specific drug classes are likely to increase migraine disease progression risk.